Lived experiences and informed behavior change among premenopausal women in a group exercise trial: a qualitative inquiry - Hadfield, Jaclyn Inel; Hulteen, Ryan; Parsons, Jenna; Allaway, Heather (Frontiers in Aging, 2025)
IntroductionBefore menopause, women experience declines in physical activity, which is a gendered phenomenon. This study explores factors that inform physical activity beliefs, behaviors, and experiences among premenopausal women participating in a group-based dance fitness workplace intervention.MethodsTwo focus groups (n = 11) were conducted with participants enrolled in a 6-week group-based dance fitness trial. A narrative inquiry using thematic analysis was used to identify themes to contextualize the experience participants had within the context of the intervention.ResultsThere were lived experiences that informed participants’ intervention experience, namely, a desire for exercise consistency and a historically negative relationship with exercise. Women consistently reported that the exercise done in the intervention was fun and brought feelings of social connectedness and comfort, thus positively impacting their experiences. These encounters led to the reporting of changes in behavior, perceived health outcomes, and perceptions of exercise, which positively influenced their intention to continue being physically active.ConclusionThis study provides an understanding of intervention strategies and lived experiences that may be useful to improve the physical activity behaviors and health of women before menopause occurs. Physical activity programs incorporating women’s lived experiences and unique preferences may align with the exercise women report a desire to have in their lives.